X-ray shapes of elliptical galaxies and implications for self-interacting dark matter. Issue 5 (10th May 2021) - McDaniel, A.; Jeltema, T.; Profumo, S.
Abstract: Several proposed models for dark matter posit the existence of self-interaction processes that can impact the shape of dark matter halos, making them more spherical than the ellipsoidal halos of collisionless dark matter. One method of probing the halo shapes, and thus the strength of the dark matter self-interaction, is by measuring the shape of the X-ray gas that traces the gravitational potential in relaxed elliptical galaxies. In this work we identify a sample of 11 relaxed, isolated elliptical galaxies and measure the ellipticity of the gravitating matter using X-ray images from the XMM-Newton and Chandra telescopes. We explore a variety of different mass configurations and find that the dark matter halos of these galaxies have ellipticities around ϵ ≃ 0.2-0.5. While we find non-negligible scatter in the ellipticity distribution, our results are consistent with some degree of self-interaction at the scale of σ/ m ∼ 1 cm 2 /g, yet they also remain compatible with a cold dark matter scenario. We additionally demonstrate how our results can be used to directly constrain specific dark matter models and discuss implications for current and future simulations of self-interacting dark matter models.